Atividade antibacteriana de floroglucinóis e do extrato hexânico de Hypericum brasiliense Choysi Antibacterial activity of the phloroglucinols and hexanic extract from Hypericum brasiliense Choysi - Hildegardo Seibert França; Ricardo Machado Kuster; Priscila da Nóbrega Rito; Adriana Passos de Oliveira; Lenise Arneiro Teixeira; Leandro Rocha (Química Nova, 2009)
Three phloroglucinols were obtained from Hypericum brasiliense: japonicine A (1), isouliginosin B (2) and uliginosin B (3). Bioautography and disk diffusion methods were used to determine antibacterial activity of the hexanic extract. Strains of the Coagulase Negative Staphylococcus and American Methicillin Resistant Staphylococcus aureus clones showed a growth inhibition zone ranging from 10 to 12 mm and 7 to 15 mm, respectively. Minimal inhibitory concentration (MIC) values were used to measure antistaphylococcal activity for all phloroglucinols. Isouliginosin B and uliginosin B presented MIC values of 1.5 and 3.0 µg/mL, respectively, while japonicine A displayed MIC value of 50.0 µg/mL.